(untitled) (E Conference Zone, 2022)
This article talks about the methodological foundations of improving the information and communication potential of future vocational education teachers in the current information age based on computer design tools. The model of the process of improving the information and communication potential of future vocational education teachers with the help of computer design tools includes the following components: motivational-value, substantive, operational-management, reflexive-resultative.